¿Cómo se han vivido estas transformaciones? ¿Qué queda por hacer? (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2017)
This paper contains the main changes lived in the Economy, the Law and the corporations, as a result of an inquiry done to experts of different institutions, universities and companies. It also includes the changes that are necessary to do in the short term.
Keywords: Economy; Business; Law; changes